Angela Markado - Lacaba, Jose F.; Coronel, Hilda; Delgado, Johnny; Rodriguez, Celia; Caparas, Carlo J.; Brocka, Lino; Four Seasons Film International(Firm). ([Pace of production not identified] Four Seasons Film International, 1980)
"Angela Delmar (Hilda Koronel) works as a waitress for one of the seedier bars in Manila. There she meets five patrons of the bar, who also turn out to be a gang specializing in drugging and raping girls and later on selling them to prostitution. Angela is the only one tending to her mother, a laundrywoman who stopped working due to tuberculosis. One night, she gets kidnapped, raped, and kept for five days by the five men. The men tattoo their names on the back of Angela, before selling her to a brothel. Angela escapes, and is taken in by a kindly hostess (Celia Rodriguez). However, upon returning to her home, she discovers her mother has died, her best friend has also been raped by the same five men and later on committed suicide. From then on, she makes it her life's mission to kill the five men by wearing wigs and costumes, and stalking the men with a handy switchblade".--written by Gay Filipino Soldier
"Summary taken from https://www.imdb.com/title/tt0295854/?ref_=fn_al_tt_1
Produced by Maria Vargas Montilibano; music by Jeric Soriano; cinematography by Conrado Baltazar.
Hilda Coronel, Johnny Delgado, Celia Rodriguez.
DVD
In Tagalog.
Keywords: Drama; Crime; Thriller